An exploration into the concept of âassisting with sinsâ in imami jurisprudence opinions - Ã˜Â´Ã›ÂŒÃ˜Â® Ã˜Â§Ã™Â„Ã˜Â§Ã˜Â³Ã™Â„Ã˜Â§Ã™Â…Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã˜Â¹Ã™Â„Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The notion âassisting with sinsâ is a rule founded upon argumentations from the Qurâan and tradition, reason and consensus, and its authority is unassailable. There is almost no dispute as regards its authority, whereas the implications of the term have always been controversial and contested among the jurists. What has been considered as important in this research is the study of the history and transformation of Shiite jurisprudential views on this issue from the beginning. For this purpose, a descriptive analytical method has been adopted based on the application of library documents. A look at the opinions of jurists demonstrates how greatly diverse they are as regards their different definitions of âassisting with sinsâ, where most of those definitions are based on conventional understanding. On how to adapt the concept of âassistingâ with conventional understanding, various criteria have been mentioned, mostly referring back to one criterion expressed and explained best by Sheikh Ansari, i.e. assisting with preliminaries whose benefits are exclusively á¸¥arÄm. Finally, based on a summary of the statements and theories, it can be concluded that in case of failure of conventional understanding as regards the problem, the criteria for a correct application of the common understanding must be intentionality of the assistant.